1997
DOI: 10.1142/s0218863597000198
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Photorefractive Characterization of BTO Crystals Doped with Cd, Ca, Ga, and V

Abstract: Single crystals of Bi12TiO20 (BTO) are grown by a modified Czochralski technique. Doping with cadmium, calcium, gallium, and vanadium is performed by adding corresponding oxides to the melt. Optical parameters like refractive index, optical absorption, optical activity, light induced absorption, electrooptic coefficient, and photoconductivity are determined. Photorefractive properties of the samples are characterized with the help of a conventional two-beam interference setup. Diffraction efficiency and decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…4. This value is in agreement with previously reported values of 1.1 eV [25,26], 1.06 eV [10], and 0.99 eV [7], among others.…”
Section: Dark Relaxationsupporting
confidence: 94%
See 1 more Smart Citation
“…4. This value is in agreement with previously reported values of 1.1 eV [25,26], 1.06 eV [10], and 0.99 eV [7], among others.…”
Section: Dark Relaxationsupporting
confidence: 94%
“…Bi 12 TiO 20 (BTO) is particularly interesting among sillenites because it exhibits the lowest (about 11°/mm at 514.5 nm wavelength) optical activity. Sillenites in general and BTO in particular show a relatively strong light absorption as well as a pronounced lightinduced absorption (photochromic) effect [4][5][6][7][8][9][10] in the visible wavelength range. Absorption is in general inconvenient for holographic recording because it reduces the level of light available for recording.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another salient feature of bismuth titanate is the significant photoinduced absorption in the visible range [2,[8][9][10][11][12][13][14][15], which is believed to result from photoinduced charge transfer between defect centers with different photoionization cross sections [8][9][10][11][12][13][14]. The concentration of such centers, the probabilities of the photoexcitation and thermal generation of nonequilibrium charge carriers and intracenter transitions, and recombination coefficients govern the dynamics and magnitude of photoinduced absorption [15] and may depend on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In [5][6][7][8] it was demonstrated that impurities influence significantly the photorefractive parameters of bismuth titanium oxide. This can be caused by the fact that doping of the BTO crystals can cause the occurrence of new deep energy levels and the change of the structural defect parameters characteristic of undoped samples [9].…”
Section: Introductionmentioning
confidence: 99%
“…The significant absorption in the Bi 12 TiO 20 : Ca crystal limits its application for a photorefractive material in devices using laser radiation with wavelengths of 532, 514.5, and 488 nm. The shoulder is absent or its intensity is insignificant for the BTO crystals doped by Al, Ga, Zn, P, Cd, and V [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%